PERAN KELEMBAGAAN LOKAL ADAT DALAM PEMBANGUNAN DESA - Wedy Nasrul (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The role of public and institute in development of countryside is not only limited to beneficial owner, but actively involved direct in development programs. Condition of local institute of custom here and now will affect to the role in development of countryside. Purpose of fundamental of this research description the role of local institute of custom in development of countryside. This research applies qualitative method with case study in Nagari Sungai Pua Kecamatan Sungai Puar Kabupaten Agam. Data collecting is done qualitatively, that is direct observation or observation, in-depth interview and documentation. Research finding indicates that as result of governmental intervenes to government of nagari from time to time indirectly makes the role of local institute of custom on the wane in development of countryside. The role of local institute of custom in development of nagari still there is in each development step countryside, where a real role dominance is at planning stage and coordination.